Measuring Cultural Diversity at a Regional Level - Dirk Dohse; Robert Gold (WWWforEurope, 2013)
This paper discusses alternative measures of cultural diversity to be used in subsequent investigations of the impacts of cultural diversity on regional development in Europe. It derives indicators for the measurement of cultural diversity from the literature and describes possible adjustments and refinements. Finally, the discussed measures and weights are applied in order to provide a first descriptive overview of cultural diversity in in Europe at the regional (NUTS-2) level.
Keywords: M13; O18; R11; 330; Regional development; cultural diversity; measurement issues